The Effect of Return on Assets, Current Ratio, Debt to Equity, and Net Profit Margin on the Share Prices of Non-Cyclicals consumer goods Companies Listed on the Bei During the 2021-2023 Period - Indah Julita Sianipar; Brina Manalu; Sasysha Dera; Jenny Zain; Oky Syahputra (Indonesian Journal of Business Analytics, 2026)
Changes in the Stock Price are not only a reflection of the  , but also the result of a complex interaction of various internal and external factors that affect investors' perception of the Company's prospects. Internally, economic key figures such as profitability (net profit margin), liquidity (current ratio), asset utilization (return on assets), and financing structure (debt ratio) provide essential information about the stability of the business and the ability to generate profits. This study uses a quantitative approach with secondary data. A multiple linear regression analysis was used to examine the data. According to the study results, the ROA variable significantly influences the cost of shares. in contrast to CR, DER, NPM has no effect on stock prices. This shows that investors should be able to consider other factors as the basis for stock investment. These findings indicate that the company should improve its economic performance in order to attract capital investors in the financial market. The actual consequence is hat the company has the ability to manage resources effectively to generate profits. maximum return and thus strengthen investors' confidence.